Finding Talent: What Does Talent Management Require in Order to Change? - Rosari, Reni; Danarilia, Vania Olivine; Ardianto, Heni (Ilomata International Journal of Management, 2024)
This study examines the concept of “talent management for change” through a comprehensive review and mapping of the literature from a multilevel perspective. It utilizes published journals sourced from the Publish or Perish (PoP) database based on Google Scholar, with a subsequent elimination process to ensure relevance and credibility, including only those indexed by Scopus. The literature review reveals current research trends related to organizational change in talent management. Additionally, it identifies key variables and suggests future research directions from a multilevel perspective. A limitation of this study is its reliance on data from sources with high credibility and Scopus indexing, included based on their relevance. For the implication, this literature review offers conceptual and practical insights into talent management for change, providing a general overview and identifying specific needs. Furthermore, it enhances understanding of the topic and offers guidance for future research. This study maps existing research in published journals concerning talent management for change, highlighting its relevance and identifying essential elements for managing talent in the context of change.